2007
DOI: 10.1038/nsmb1298
|View full text |Cite
|
Sign up to set email alerts
|

Myosin-V makes two brownian 90° rotations per 36-nm step

Abstract: Myosin-V processively walks on actin filaments in a hand-over-hand fashion. The identical structures of the heads predict a symmetric hand-over-hand mechanism where regular, unidirectional rotation occurs during a 36-nm step. We investigated this by observing how fixed myosin-V rotates actin filaments. Actin filaments randomly rotated 90 degrees both clockwise and counter-clockwise during each step. Furthermore, ATP-dependent rotations were regularly followed by ATP-independent ones. Kinetic analysis indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…This flexibility in the rotation angle may be functionally advantageous, as it should help myosin avoid any obstructions in the crowded actin network of a cell by allowing it to adopt to different conformations to maximize the probability that the heads will alternate between the lead and rear positions during motility. Our model can also explain why in our previous study (21) an actin filament underwent two 90°Brownian rotations per 36 nm myosin V step, while in the present study only one 90°rotation was seen. In the previous study, myosin V was fixed onto a glass surface at its tail end, whereas in this one the tail end is free.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…This flexibility in the rotation angle may be functionally advantageous, as it should help myosin avoid any obstructions in the crowded actin network of a cell by allowing it to adopt to different conformations to maximize the probability that the heads will alternate between the lead and rear positions during motility. Our model can also explain why in our previous study (21) an actin filament underwent two 90°Brownian rotations per 36 nm myosin V step, while in the present study only one 90°rotation was seen. In the previous study, myosin V was fixed onto a glass surface at its tail end, whereas in this one the tail end is free.…”
Section: Discussionsupporting
confidence: 50%
“…We previously found that a fluorescently labeled actin filament can be rotated by myosin V fixed to a glass surface (21). In the present study, we directly observed myosin rotations by simultaneously measuring myosin steps and orientations, finding myosin V rotates 90°for each 36 nm step.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The behavior of kinesin is in sharp contrast with a distantly related processive motor that is also known to move hand-overhand, myosin-V, which has recently been reported to undergo random, Ϯ90°stalk rotations per step (32), indicating that the heads indiscriminately take left and right steps. The source of these rotations was attributed to accumulation and relief of torsional strain within the otherwise rigid dimer.…”
Section: Discussionmentioning
confidence: 77%
“…Recently, the diffusive motion of unbound myosin V heads has been directly observed during the stepping process ( Dunn & Spudich 2007;Shiroguchi & Kinosita 2007). The random twisting motion of the neck domain around its axis was observed associated with the step movement (Komori et al 2007).…”
Section: Processive Movement Of Unconventional Myosinsmentioning
confidence: 99%